Absorption by an Optical Dipole Antenna in a Structured Environment - E. Castanié; R. Vincent; R. Pierrat; R. Carminati (International Journal of Optics)
We compute generalized absorption and extinction cross-sections of an optical dipole nanoantenna in a structured environment. The expressions explicitly show the influence of radiation reaction and the local density of states on the intrinsic absorption properties of the antenna. Engineering the environment could allow to modify the overall absorption as well as the frequency and the linewidth of a resonant antenna. Conversely, a dipole antenna can be used to probe the photonic environment, in a similar way as a quantum emitter.